Survival, Integration, and Differentiation of Unrestricted Somatic Stem Cells in the Heart. Issue 1 (January 2013) - Ding, Zhaoping; Burghoff, Sandra; Buchheiser, Anja; Kögler, Gesine; Schrader, Jürgen
Unrestricted somatic stem cells (USSCs) derived from human umbilical cord blood represent an attractive cell source to reconstitute the damaged heart. We have analyzed the cardiomyogenic potential and investigated the fate of USSCs after transplantation into rat heart in vivo. USSCs demonstrated cardiomyogenic differentiation properties characterized by the spontaneously beating activity and the robust expression of cardiac α-actinin and troponin T (cTnT) at protein and mRNA level after cocultivation with neonatal rat cardiomyocytes. To study the fate in vivo, eGFP + USSCs were injected transcoronarily into immunosuppressed rats via a catheter-based technique. Nearly 80% USSCs were retained within the myocardium without altering cardiac hemodynamics. After 7 days, 20% of the transplanted cells survived in the host myocardium and showed elongated morphology with weak expression of cardiac-specific markers, while some eGFP + USSCs were found to integrate into the vascular wall. After 21 days, only a small fraction of USSCs were found in the myocardium (0.13%); however, the remaining cells clearly exhibited a sarcomeric structure similar to mature cardiomyocytes. Identical results were also obtained in nude rats. In addition, we found some cells stained positively for activated caspase 3 paralleled by the massive infiltration of CD11b + cells into the myocardium. In summary, USSCs can differentiate into beating cardiomyocytes by cocultivation in vitro. After coronary transplantation in vivo, however, long-term survival of differentiated USSCs was rather low despite a high initial fraction of trapped cells.